Comparison of Sunshine Duration Measurements between the Campbell–Stokes Sunshine Recorder and Three Automatic Sensors at Three Locations in Cyprus - Pashiardis, Stelios; Pelengaris, Alexandros; Kalogirou, Soteris A. (My University, 2023)
This paper compares the daily sunshine duration (SD) measured by the Campbell–Stokes sunshine recorder (CS) with three automatic instruments (Kipp & Zonen pyranometers (CM6 B), pyrheliometer (CHP1) and CSD3 sunshine recorders). The comparisons are essential, since recently, automatic sunshine duration sensors have been replacing the manual measurements, affecting, therefore, the continuity of the CS time series. The comparisons were applied to the daily SD data of three synoptic stations (Larnaca A/P, Pafos A/P and Athalassa) where parallel measurements of manual and automatic instruments are carried out during the periods 2009–2012 and 2012–2015. The CSD3 measurements were obtained from two automatic weather stations (AWSs) which are close to the synoptic station of Larnaca A/P. The comparisons referred to the daily and monthly sums of sunshine duration, as well as to their statistical distributions and their relationships. The daily differences in the pairs of sunshine recorders installed at the same location are mostly within the range of −1.0 to +1.0 h. At Larnaca, in the period 2009–2012, the pyranometric method’s (Gl) values were higher than the CS in the summer months. Pafos and Athalassa showed higher values of CS compared to Gl and the pyrheliometric method (Pr), respectively, almost throughout the year. Generally, the annual average daily differences between the different pairs range between 0.3 and 0.5 h. Regression equations were determined allowing the estimation of daily SD under different sky conditions. The coefficient of determination (R2) reached the values of 0.91 and 0.96 under ‘all sky’ conditions, and between 0.80 and 0.91 under ‘clear’ sky conditions at the three locations.
Keywords: Campbell–Stokes heliograph; CSD3 sensors; Pyranometer; Pyrheliometer; Sunshine duration